Yearly incidence and pattern of very late recurrence of atrial fibrillation as detected by continuous electrocardiographic monitoring using an implantable loop recorder. (19th May 2022) - Musat, D; Milstein, N; Saberito, M; Bhatt, A; Habibi, M; Preminger, M; Sichrovsky, T; Shaw, R; Mittal, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: A very late recurrence (VLR) of atrial fibrillation (AF) is considered present when patients have their first recurrence of AF > 12 months post-ablation. Little is known about the yearly rates and patterns of VLR AF recurrence. Objective: To assess the yearly incidence and pattern of VLR in pts with AF who underwent cryoballoon (CB) pulmonary vein isolation (PVI). Methods: We prospectively enrolled consecutive patients with AF who underwent CB PVI and had an implantable loop recorder (ILR) inserted up to 3 months post-ablation. Patients were followed for recurrent AF (excluding a 3-month post-ablation blanking period). Results: Our cohort included 222 patients (66 ± 9 years; 143 [64%] male; 120 [54%] paroxysmal AF; CHA2DS2-VASc 2.6 ± 1.6). At 1-year, 111 (50%) patients remained free of AF. Two-year follow-up was available in 95 of these patients; 62 (65%) remained in sinus. Three-year follow-up was available in 42 of these patients; 36 (86%) remained in sinus (Figure). Of the 39 patients who developed AF after initially being free of AF for at least 1-year post ablation, 24 (62%) patients had either a frequent or persistent pattern of AF. Conclusions: Our data show that the greatest likelihood of failure following a CB PVI occurs in the first year of ablation. The rate of failure becomes lower year by year. These data suggest that long term outcome may be driven more by the initial ablation as opposed to progressive evolution of the patient's substrate